Development of an automatized system for a gamma scanning technique - Rodríguez-Méndez, Francisco (2019)
Non-destructive testing techniques have proven to be a powerful tool in the study and characterization of materials. This work presents the development of an automated measurement system based on the attenuation of gamma radiation for the study of materials. First, we described the design process of the electromechanical elements and the automatic control system, followed by its implementation. The results show the capacity and mechanical accuracy of the system. The resolution of the motor and the displacement capacity of the robot are 8 μm for the horizontal movement with maximum carriage travel of bi-directional 54 cm and 4 μm for vertical movement, with maximum carriage travel of bi-directional 57 cm. The system allows for a sample rotation, being the angular trajectory of 360 ° with unidirectional travel. The sensitivity of the system for detecting specific changes in the thickness of the material is verified statistically, also evaluating the sampling periods to obtain a measurement with precision. The relative error of the measurements is determined and its causes and solutions are discussed.